Xuebijing Injection Alleviates Pam3CSK4-Induced Inflammatory Response and Protects Mice From Sepsis Caused by Methicillin-Resistant Staphylococcus aureus - Li, Tiantian; Qian, Yiming; Miao, Zhulei; Zheng, Peiyong; Shi, Ting; Jiang, Xinru; Pan, Lingyun; Qian, Fenghua; Yang, Guizhen; An, Huazhang; Zheng, Yuejuan (Frontiers in Pharmacology, 2020)
A leading cause of death worldwide is sepsis that develops as a dysregulated immune response to infection. Serious infection caused by methicillin-resistant Staphylococcus aureus (MRSA) increases the difficulty of treatment in septic patients. Host-directed therapy (HDT) is an emerging approach for bacterial infections. Xuebijing injection (XBJ), a commercialized injectable prescription from traditional Chinese medicine, has been used as an adjuvant therapy for sepsis with a history of 15 years. Whether it plays a protective role in severe infection caused by antibiotic-resistant bacteria is still unknown. In this study, XBJ significantly improved the survival of MRSA-induced sepsis mice. In MRSA-infected mouse model, XBJ down-regulated the expression of inflammatory cytokines IL-6, TNF-α, MCP-1, MIP-2 and IL-10 in sera, decreased bacterial load in spleens and livers, and alleviated tissue damage of lung, liver and kidney. The combination of XBJ with vancomycin or dexamethasone exhibited a better down-regulatory role of inflammatory response. Then, the protective mechanism of XBJ was further investigated. XBJ inhibited heat-killed MRSA-induced IL-6 and TNF-α production in mouse macrophages, and decreased Pam3CSK4 (a synthetic tripalmitoylated lipopeptide mimicking bacterial lipoproteins)-stimulated expression of IL-6, TNF-α, IL-1β, IL-12, etc. in mouse macrophages. Furthermore, XBJ down-regulated the activation of NF-κB, MAPK and PI3K/Akt pathways in Pam3CSK4-stimulated mouse macrophages. In conclusion, our findings demonstrated that XBJ played a protective role in MRSA-challenged mice and down-regulated the activation of inflammatory response and signalling pathways initiated by Pam3CSK4. It enlarged the clinical application of XBJ in the treatment of severe bacterial infection, e.g. caused by MRSA.